Coupling dalapon biodegradation with electricity generation in microbial fuel cells - Sarioglu, Yagiz; Sever-Kaya, Dilek; Kurt, Halil; Kantarci-Carsibasi, Nigar; Kul, Aykut; Marakli, Sevgi; Catal, Tunc (ELSEVIER SCI LTD, 2026)
Dalapon (2,2-dichloropropionic acid) is a persistent halogenated herbicide frequently detected in aquatic environments, yet its bioelectrochemical degradation has not been previously demonstrated. This study reports the simultaneous biodegradation of dalapon and electricity generation in single-chamber microbial fuel cells inoculated with the psychrotolerant Antarctic isolate Psychrobacter sp. TaeBurcu001. While mixed microbial cultures alone were unable to oxidize dalapon as the sole added carbon source, co-inoculation with TaeBurcu001 enabled measurable electricity generation (0.1-0.21 V at 980 Omega) and achieved more than 90% dalapon removal. Targeted LC-MS/MS analysis confirmed substantial dalapon degradation under all tested conditions. Microbial community analysis based on 16S rRNA gene sequencing revealed enrichment of electrogenic and xenobiotic-degrading genera, including Xanthobacter, Pseudomonas, Achromobacter, and Dysgonomonas. Molecular docking and molecular dynamics simulations suggested favorable binding of dalapon within the catalytic pocket of L-2-haloacid dehalogenase, supporting a plausible enzymatic contribution to dehalogenation. Overall, this study demonstrates
Keywords: Microbial biotechnology; Microbial community; Pesticides; Molecular docking; Molecular Dynamics; REFRACTORY ORGANIC PESTICIDE; BIOELECTRICITY GENERATION; SIMULTANEOUS DEGRADATION; DEHALOGENATION; COMMUNITY; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels